2019
DOI: 10.1177/1753193419882853
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes after in situ cubital tunnel decompression: a report in 77 patients

Abstract: This prospective single-centre study describes the patient-reported outcomes following open in situ decompression for cubital tunnel syndrome. The Quick version of the Disabilities of the Arm, Shoulder and Hand questionnaire and patient satisfaction scores were collected over a 3-year period. Outcomes were available for 77 patients at a mean of 17 months (11–27 months) postoperatively. The mean scores improved significantly from 39 to 30 postoperatively. The score change correlated strongly and significantly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…17,31 Postoperative DASH scores have also been shown to correlate with patient satisfaction, and patients with muscle weakness and atrophy before surgery had poorer scores. 32 Moreover, it is increasingly recognized that PROs may more accurately reflect a patient’s level of disability from disease than clinical or radiographic measurements for a variety of problems in hand surgery. 33,34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,31 Postoperative DASH scores have also been shown to correlate with patient satisfaction, and patients with muscle weakness and atrophy before surgery had poorer scores. 32 Moreover, it is increasingly recognized that PROs may more accurately reflect a patient’s level of disability from disease than clinical or radiographic measurements for a variety of problems in hand surgery. 33,34…”
Section: Discussionmentioning
confidence: 99%
“…22,25,40 This type of irreversible injury appears to occur more commonly in UNE than carpal tunnel syndrome and is associated with poorer surgical outcomes, residual symptoms, and decreased patient satisfaction. 12,16,32,41 Although abnormal thresholds for CMAP amplitude have been established, these measurements are not routinely used in conventional evaluation of UNE. 20,25,42 Although many authors have argued that EDXs add little value in the workup of carpal tunnel syndrome, [43][44][45][46] we would posit the contrary in the context of UNE.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high frequency of surgical treatment for CuTS, comparison of outcomes of cubital tunnel release remains difficult due to the heterogeneity of PROMs used. 17,18 A recent systematic review of 101 studies reported that 30 different patient or clinician reported instruments were used to assess surgical treatment for CuTS within the literature. 7 Popular existing questionnaires used for hand conditions include Michigan Hand Questionnaire (MHQ); Disabilities of the Arm, Shoulder, and Hand (DASH); and the Carpal Tunnel Questionnaire (CTQ).…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were done under the care of a single consultant hand surgeon with level V experience (Tang and Giddins, 2015). An open in-situ decompression was performed without transposition of the ulnar nerve in accordance with a previously published technique (Yeoman et al., 2020). Some of the patients in this study had been included in a previous smaller study that did not address the same research question (Yeoman et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…An open in-situ decompression was performed without transposition of the ulnar nerve in accordance with a previously published technique (Yeoman et al., 2020). Some of the patients in this study had been included in a previous smaller study that did not address the same research question (Yeoman et al., 2020). We have reported the demographic details of the patients who were not included in the previous study (Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%